1999
DOI: 10.1177/00220345990780080901
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Masseter EMG Activity of Healthy Subjects in a Natural Environment

Abstract: Facial pain of patients with craniomandibular disorders might be caused by muscle overload. However, the activity of masticatory muscles of healthy individuals is still unknown. The aim of this study was therefore a first attempt to clarify this question by recording the masseter muscle activity of healthy subjects during sleep by means of portable recorders. The study was performed on 21 healthy subjects selected after telephone and questionnaire screenings and clinical examination from among randomly selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(123 citation statements)
references
References 40 publications
8
111
0
4
Order By: Relevance
“…5, 19-22 The numbers of clenches per night in each diagnostic group were similar to previous reports for bruxer and non-bruxer groups. 20 Mean durations of clenching behavior in the current study was similar to some previously reported data 8 but shorter compared to other reports.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…5, 19-22 The numbers of clenches per night in each diagnostic group were similar to previous reports for bruxer and non-bruxer groups. 20 Mean durations of clenching behavior in the current study was similar to some previously reported data 8 but shorter compared to other reports.…”
Section: Discussionsupporting
confidence: 89%
“…20 Mean durations of clenching behavior in the current study was similar to some previously reported data 8 but shorter compared to other reports. 19, 21, 22 The latter differences may be attributed to different EMG amplitude threshold criteria used to define onset and duration of clenching. The results suggested that all subjects generally activated their temporalis muscles at low magnitudes at night, but average duration of activation was longer in +DD+P than -DD-P subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Weaver and Co., Nucla Way, Au, CO, USA) and rubbed with grinding paper to reduce impedance, surface EMG signals were obtained using 10-mm bipolar gold surface electrodes (Nicolet Biomedical, Madison, WI, USA) with a 2-cm electrode distance. 12 Conductive paste (Ten20 TM , D.O. Weaver and Co.) was applied and the electrodes were attached and secured by adhesive pads (Omnifix Ò , Unitex-Hartmann S.A., Mataro´, Barcelona, Spain).…”
Section: Emg Activity Analysismentioning
confidence: 99%
“…Limitations of this method include being less accurate than tests using intramuscular needle electrodes, and sensitivity to external factors such as incorrect preparation of skin surface, salivary fistula in the chin area, excessive sweating, nonhealing wounds, or uncontrolled saliva dribbling from the mouth. The advantage of surface electromyography is the ability to compare ratings of bioelectrical activity in balance, and during intensive muscle work [34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%